Seasonal Study for Habitat of Myriophyllum spicatum L. in Al-Burgga Marsh, Hor Al-Hammar, Southern Iraq (Baghdad Science Journal, 2014)
Myriophyllum spicatum distribution in Al-Burgga marsh, Hor Al-Hammar was described in relation to some of the physical-chemical properties for its habitat (water depth, light penetration, water temperature, water salinity, pH, dissolved oxygen, Ca+2, Mg+2, reactive NO2=, reactive NO3-1, and reactive PO4-3) during 2011, seasonally. CANOCO ordination program (CCA) was used to analyse the data. Its vegetation cover percentage was with its peak at summer, its value was 90 %, while the lowest value was 20 % in winter. Statistically, Positive relationships for WT, sal., Ca+2, Mg+2, reactive NO2=, reactive NO3-1, and reactive PO4-3 with the vegetation cover percentage were observed. While, negative relationships for WD, pH, and DO with the vegetation cover percentage were observed. Also, the negative relationship between light penetration and the vegetation cover percentage can be attributed to the water depth, which was shallow and the light penetration followed water depth and reached to the bottom during all of the period study. In addition, two species were registered with Myriophyllum spicatum community as associated species, which are Hydrilla verticillata and Ceratophyllum demersum.